Identity at Thresholds and American Dramatic Frames: Paula Vogel’s How I Learned to Drive and Edward AI bee’s The Goator Who Is Sylvia? - Cristian, Réka Mónika (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The aim of this essay is to explore the thresholds of identity in Paula Vogel’s How I Learned to Drive (1997) and Edward Albee’s The Goat or Who Is Sylvia? (2002). These works are highly controversial plays written by a lesbian and a gay playwright; they have shocked the American audience but were awarded afterwards with the Pulitzer Prize and the Tony Award for best Play, respectively. Another, earlier play of the same category is Tony Kushner’Angels in America (1991 and 1992). Here the author stages an image of America where “religious, racial, sexual identities co-exist and intermingle” (Bigsby, Modern 423) in order to shape a world in which “the breaching of boundaries is both method and subject” (423). The transgression of boundaries in Kushner’s play happens mainly in the context of gender and political issues; he depicts AIDS, race and homosexuality, the versatile topics of the eighties and nineties, in a straightforward, outspoken manner comparable only to the world of Vogel’s and Albee’s plays.